Identification of a major glucose transporter in Flavobacterium johnsoniae: Inhibition of F. johnsoniae colony spreading by glucose uptake. (30th August 2018) - Imamura, Keigo; Sato, Keiko; Narita, Yuka; Kondo, Yoshio; Nakane, Daisuke; Naito, Mariko; Fujiwara, Taku; Nakayama, Koji
ABSTRACT: Many members of the phylum Bacteroidetes, such as Flavobacterium johnsoniae, can glide over a solid surface: an ability called gliding motility . It can be usually observed on agar plates as thin, flat, spreading colonies with irregular, feathery edges; this phenomenon is called colony spreading . Colony spreading of F. johnsoniae on 1.5% agar plates containing poor nutrients is dose‐dependently inhibited by addition of D‐glucose, as previously reported. Accordingly, here, we created mutants (by transposon mutagenesis) that partially suppressed glucose‐mediated inhibition of colony spreading. Among the isolates, we found that one had a transposon insertion in Fjoh_4565, tentatively named mfsA, which encodes a major facilitator superfamily (MFS) transporter previously shown to be required for growth on glucose, N‐acetyl‐glucosamine, and chitin. We constructed an mfsA deletion mutant and found that the mutant showed no glucose‐mediated acceleration of growth or glucose uptake. The mfsA gene complemented the phenotype of a glucose‐negative Escherichia coli . These results suggest that the mfsA gene encodes the sole MFS transporter of glucose in F. johnsoniae and that glucose uptake is partially required for the glucose‐mediated inhibition of F. johnsoniae colony spreading.